On the social and religious status of an Indian astrologer at the royal court - Beinorius, Audrius (Acta Orientalia Vilnensia, 2008)
Vilnius UniversityThe object of this paper is to investigate the social and religious status of an astrologer at the royal court and his relation to royal priests in medieval Indian society. This paper is confined to the social and religious role of an astrologer as it was perceived by members of society, both practicing astrologers and non-astrologers. By consulting different primary sources (i.e., jyotiḥśāstras, dharmaśāstras, purāṇas and epics), one can have some appreciation of various issues regarding, for example, the conditions in which royal astrologers operated, their duties and royal supporters, the salaries they obtained, and many other similar matters of extreme importance for the location of the astrologer within the larger social panorama. The conclusion is made that in India by the Epic times, at least, the astrologer had become one of the six principal officials of the royal court and gradually assumed some of the duties of the royal priest (purohita). In India even the position of royal astrologer had its sanction in myth. Astrology, therefore, was considered divine in origin as well as in its subject matter. The court astrologer was considered indispensible to the king and to the welfare of the kingdom. The astrologer had enormous power and responsibility at the royal court and at every level of society. The astrologer was fulfilling his role as an institutional authority by providing knowledge and understanding to the royal court and society. Indian astrologers had to depend on a patronage system for their sustenance, and they seem to have exploited that system with some success.